The Role of Content Marketing in Brand Loyalty: An Empirical Analysis - Siti Julaeha, Lia (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research investigates the role of content marketing in building brand loyalty through an empirical analysis. It evaluates the effectiveness of various content marketing strategies, including informative articles, engaging videos, and interactive social media posts, in enhancing consumer loyalty. The study emphasizes the importance of consumer engagement, perceived value, and two-way communication in fostering brand loyalty. Informative articles are valued for their ability to provide useful information and build trust. Engaging videos create emotional connections and memorable experiences, while interactive social media posts encourage active participation and community building. The perceived value of content, defined by its usefulness, relevance, and quality, is critical in determining consumer engagement and loyalty. Two-way communication, involving reciprocal interactions between brands and consumers, plays a pivotal role in building loyalty. It enhances engagement by facilitating direct dialogue, personalizing interactions, and effectively addressing consumer feedback and concerns. The research concludes that brands should focus on robust communication channels, personalized content, and active feedback mechanisms to strengthen consumer relationships.